Integration of Information and Communication Technology in Educational Administration Management at School - Riinawati, Riinawati (JURNAL AL-TANZIM, 2024)
This research aims to analyze the application of Information and Communication Technology (ICT) in educational administration management, focusing on increasing the system's efficiency and effectiveness at SMA Negeri 6 Banjarmasin. This research was conducted by identifying the use of ICT in the educational administration process, evaluating the benefits and challenges faced in its application, and analyzing its impact on the efficiency and effectiveness of the administration system. The research method used is a qualitative approach with case studies. Data was collected through interviews, observation, and documentation. The collected data was then analyzed thematically. The research results show that SMA Negeri 6 Banjarmasin has implemented various information and communication technologies, such as student database systems, attendance management applications, and digital communication platforms. The application of ICT provides several benefits, including reducing the time and energy required for administrative tasks, increasing the accuracy and speed of data processing, and strengthening communication between related parties. This research provides implications regarding the importance of maintaining and continuing to develop the application of information and communication technology in schools. Regular evaluation and system updates, as well as training for users, are critical factors in maintaining the benefits obtained from the application of ICT.